The Role Of Product Quality Implementation In The Success Of Operational Activities In Tenants Guarded By The Information Technology Business Incubator Maleo Techno Center - Astrid Wahdini; Sulaeman Miru; Syamsuddin Syamsuddin; Kadek Agus Dwiwijaya (UNIVED Press, 2026)
The implementation of product quality is important in the success of operational activities in tenants fostered by the information technology business incubator. This study aims to analyze the implementation of product quality in the success of operational activities in tenants fostered by the Maleo Techno Center Information Technology Business Incubator. This study was conducted on tenants fostered by the Maleo Techno Center Information Technology Business Incubator by applying a qualitative descriptive method through interviews by assessing eight dimensions of quality according to David A. Garvin. The results of this study indicate that the eight dimensions of quality, namely the dimensions of performance, features, reliability, suitability, durability, service capability, aesthetics, perceived quality have been implemented effectively, but the performance dimension is the most dominant dimension and has a direct influence on operational success. The implementation of product quality in the incubation program not only helps tenant business development, but also creates a sustainable impact.